Filsafat Ilmu Dalam Bimbingan Dan Konseling: Menjawab Tantangan Etis Dan Ilmiah Di Era Digital - Laili, Wardatus Sholihah Nur; Prasetya, Akhmad Fajar (CV. SINAR HOWUHOWU, 2025)
The rapid development of digital technology has significantly transformed the practice of Guidance and Counseling (GC), particularly through online counseling services, digital media use, and the application of artificial intelligence. While these advancements enhance accessibility and efficiency, they also raise ethical and scientific challenges that may undermine the scientific identity of GC. Therefore, a reflective framework is needed to reaffirm the scientific foundations and humanistic values of counseling practice in the digital era.This study aims to analyze the role of philosophy of science in Guidance and Counseling as a reflective foundation for addressing ethical and scientific challenges in the digital era. A literature review method was employed by examining scholarly books and peer-reviewed journal articles related to philosophy of science, professional ethics, and technology-based counseling practices. Data were analyzed qualitatively using content analysis to identify ontological, epistemological, and axiological dimensions relevant to digital counseling practices.The findings indicate that philosophy of science plays a crucial role in ensuring that counseling practice continues to view individuals as holistic subjects, maintains the validity of counseling knowledge, and upholds ethical and humanistic values in the use of technology. In conclusion, the integration of digital technology in Guidance and Counseling must be accompanied by philosophical reflection to ensure that counseling practices remain scientific, ethical, and human-centered.